African forage plant genetic resources, evaluation of forage germplasm and extensive livestock production systems. Proceedings of the third PANESA workshop - Dzowela, B.H. (International Livestock Centre for Africa, 1988)
This proceeding report is divided in three sessions. In the first session papers on African forage plant genetic resources in Zimbabwe, Botswana, Malawi and the PANESA region are presented. The second session discusses forage germplasm evaluation. In this session experiences of ILCA, Tanzania, Mauritius, Uganda, Malawi, Ethiopia and Kenya are presented. Species involved in the studies included Brachiaria, Cynodon, Trifolium, Lablab, Zornia, Stylosanthes and Crotalaria. The third session deals with extensive livestock production systems. Experiences from Mozambique, Kenya, Tanzania, Zambia, Nigeria and Ethiopia are examined.